2021
DOI: 10.5194/hess-25-17-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18 satellite- and model-based soil moisture products using in situ measurements from 826 sensors

Abstract: Abstract. Information about the spatiotemporal variability of soil moisture is critical for many purposes, including monitoring of hydrologic extremes, irrigation scheduling, and prediction of agricultural yields. We evaluated the temporal dynamics of 18 state-of-the-art (quasi-)global near-surface soil moisture products, including six based on satellite retrievals, six based on models without satellite data assimilation (referred to hereafter as “open-loop” models), and six based on models that assimilate sat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
123
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(138 citation statements)
references
References 187 publications
(241 reference statements)
14
123
1
Order By: Relevance
“…Overall, the merged SM products showed better performances than their source datasets; they also showed the ability to capture large-scale drought events, as well as reasonable spatiotemporal patterns and climatic response characteristics. The ranges of https://doi.org/10.5194/essd-2021-84 (Figures 2 and S5) were broadly within the estimates reported by previous SM evaluations, although making a strict comparison is difficult because of the widely different spatiotemporal coverages and resolutions (Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017). These results (Figures 2 and S5) demonstrated that the merging procedures (unweighted averaging, OLC, EC) used were effective in creating relatively accurate long-term multi-layer SM data at the global scale.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, the merged SM products showed better performances than their source datasets; they also showed the ability to capture large-scale drought events, as well as reasonable spatiotemporal patterns and climatic response characteristics. The ranges of https://doi.org/10.5194/essd-2021-84 (Figures 2 and S5) were broadly within the estimates reported by previous SM evaluations, although making a strict comparison is difficult because of the widely different spatiotemporal coverages and resolutions (Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017). These results (Figures 2 and S5) demonstrated that the merging procedures (unweighted averaging, OLC, EC) used were effective in creating relatively accurate long-term multi-layer SM data at the global scale.…”
Section: Discussionsupporting
confidence: 79%
“…Such vertical inconsistencies may be related to inconsistencies in the vertical discretization of the soil column (Tables S2-S4), soil properties in each layer, modeling of lateral flow and drainage, or other factors (e.g., Balsamo et al, 2009;Best et al, 2011;Melton et al, 2019). Previous regional or global SM evaluations (e.g., Beck et al, 2021;Karthikeyan et al, 2017;Li et al, 2020b;Wang et al, 2021a;Yuan and Quiring, 2017) rarely focused on https://doi.org/10.5194/essd-2021-84 The temporal continuity of the merged products was only examined visually in this study ( Figure 5). Although the applied concatenation procedure (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…shows the lowest performance of the three reanalyses datasets. Supporting these findings, ERA5-Land participated in a soil moisture intercomparison of 18 products against large number (826) of in situ stations and performed strongly (Beck et al, 2021).…”
mentioning
confidence: 67%
“…ERA5 variables, including soil moisture, are provided in a regular grid of 0.1 × 0.1 • , with an hourly temporal resolution [37]. This database has been validated with in situ soil moisture networks worldwide, including the IP [40]. For this study, soil moisture at 12 am and 12 pm and the three depth layers provided by ERA5 were averaged.…”
Section: Era5-land Soil Moisturementioning
confidence: 99%